The interrelationship between emotion, cognition, and bilingualism - Robinson , Crystal J.; Altarriba, Jeanette (Yearbook of the Poznan Linguistic Meeting, 2014)
Research on the representation of emotion in human memory has focused on the ways in which words that label an emotion (e.g., love, joy) or represent emotional components (e.g., death, butterfly) are learned, stored, and retrieved from memory. The current work reviews the ways in which these types of words have been distinguished from concrete and abstract words, the types of methodologies used to distinguish among word groups, and the ways in which these words are automatically processed in the bilingual speaker. While emotion words may be more readily processed and retrieved when they appear in the first language, other word types that are neutral with regards to arousal and valence may be processed similarly across languages. The current work also illustrates the ways in which this knowledge is important in advancing theories of language and cognition, attention, perception, and mental health. Future directions are discussed that elucidate the further applications of these interesting lines of research.